All‐Inorganic CsPbIxBr3−x Perovskite Solar Cells: Crystal Anisotropy Effect. Issue 10 (17th August 2020) - Zhao, Peng; Su, Jie; Lin, Zhenhua; Wang, Jiaping; Zhang, Jincheng; Hao, Yue; Ouyang, Xiaoping; Chang, Jingjing
Abstract: Understanding the crystal anisotropy effect of materials on optical and electrical properties is crucial for further comprehension of the device operating mechanism and device performance improvement. In this study, a detailed theoretical analysis is performed to explore the crystal anisotropy effect on the performance of perovskite solar cells by employing state‐of‐the‐art multiscale simulations connecting from the material (first‐principle theory) to the device (drift‐diffusion model). According to the results obtained from first‐principle calculation, the mobility and absorption coefficient of CsPbIBr2 and CsPbI2 Br along the [001] orientation are larger than those along the [100] orientation, suggesting that the transport properties and optical properties along the [001] orientation are superior to those along the [100] orientation. According to the results obtained from the drift‐diffusion model, owing to the superior optical and transport characters along the [001] direction, the optimal power conversion efficiencies (PCEs) of CsPbI2 Br (18.88%) and CsPbIBr2 (16.42%) solar cells can be obtained. In addition, the two‐terminal CsPbIx Br3‐x /silicon tandem solar cell is also investigated. By utilizing CsPbIBr2 /silicon and CsPbI2 Br/silicon tandem structures along the [001] orientation, ultrahigh efficiencies are achieved up to 26.32% and 31.39%, respectively. Therefore, the [001] crystal orientation of CsPbIBr2 and CsPbI2 Br is more suitable for further applications of optoelectronic devices. Abstract : A theoretical study of the crystal anisotropy effect on CsPbI x Br3− x perovskite solar cells is investigated by combining first‐principle calculation with the drift‐diffusion model. According to the results, by comprehensively considering the optical and electrical properties, the ultrahigh power conversion efficiencies (PCEs) of single‐junction (PCE = 18.88%) and tandem (PCE = 31.39%) CsPbI2 Br solar cells are obtained by the [001] light incident direction.